Quality assurance of Allium ursinum plant preservation - Шатохіна, Юлія Вікторівна; Сахно, Євгеній Юрійович; Сіра, Катерина Олександрівна (Technology audit and production reserves, 2015)
It is conducted research aimed at ensuring the preservation process of Allium ursinum plant which is listed in the Red Book of Ukraine on the example of Mezyn National Park. It is established samples of fifty units in measuring the height of plants Allium ursinum. Relative error of the arithmetic mean value is equal to four per cent. It was built histogram of selective distribution, which corresponds to a classic type of distribution and has a maximum, and this gives grounds to use plant height as a control index of process quality. Also it was studied the life cycle of plants and found the relationship between plant height and period of development. The control algorithm of the preservation quality of the plants is developed. The dependence can be used for quality monitoring process.